2021
DOI: 10.1055/s-0041-1731066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MYO1H Gene Polymorphism in Skeletal Class-III Malocclusion Due to Mandibular Prognathism

Abstract: Background Mandibular prognathism (MP) is a craniofacial deformity resulting from the combined effects of environmental and genetic factors. Although various linkage and genome-wide association studies for mandibular prognathism have identified multiple strongly associated regions and genes, the causal genes and variants responsible for the deformity remained ambiguous. Aim This research work was aimed to study the association between polymorphism rs10850110 of the MYO1H gene and skeletal class-III m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Atteeri A. et al demonstrated how the rs10850110 polymorphism of the MYO1H gene has a statistically signi cant association with mandibular prognathism, as the G allele of the rs marker was overrepresented compared to the A ally in cases of mandibular prognathism, concluding that the MYO1H gene is associated with an increased risk of mandibular prognathism 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Atteeri A. et al demonstrated how the rs10850110 polymorphism of the MYO1H gene has a statistically signi cant association with mandibular prognathism, as the G allele of the rs marker was overrepresented compared to the A ally in cases of mandibular prognathism, concluding that the MYO1H gene is associated with an increased risk of mandibular prognathism 50 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Dalaie et al found there was no significant correlation between rs10850110 and rs11611277 and the risk of MP in an Iranian population (Dalaie et al, 2020). A recent study analyzed the association between MYO1H rs10850110 and skeletal Class III malocclusion in 30 patients with MP and 30 skeletal Class I malocclusion controls in an Indian population (Atteeri et al, 2021). These results suggest that carrying the G allele of rs10850110 increases the risk of MP.…”
Section: Genetic Variants Associated With Skeletal Class III Malocclu...mentioning
confidence: 99%
“…Genetic and environmental factors, particularly genetic factors, may influence the development of skeletal Class III malocclusion (Dehesa‐Santos et al, 2021; Grippaudo et al, 2016; Rodríguez‐Olivos et al, 2022; Zhou et al, 2016). Many candidate genes, including MYO1H (Atteeri et al, 2021; Dalaie et al, 2020) , COL2A1 (Dehesa‐Santos et al, 2021), GHR (Tomoyasu et al, 2009), ARHGAP21 (Perillo et al, 2015), and SNAI3 (Dehesa‐Santos et al, 2021) have been reported to be associated with skeletal Class III malocclusion. However, the mechanisms by which these genes are susceptible to skeletal Class III malocclusion remain unclear (Cruz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, genetic alteration that affects the muscles could affect the skeletal growth ( Moss, 1997 ). Previous studies have linked polymorphisms in MYO1H with mandibular discrepancy in Class III malocclusion ( Da Fontoura et al, 2015 , Wise et al, 2000 , Sun et al, 2018 , Atteeri et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%